Sikap Petani Padi Terhadap Penerapan Pertanian Organik di Kecamatan Mojogedang Kabupaten Karanganyar - Ismiranda Dwi Prajatino; Suminah Suminah; Sugihardjo Sugihardjo (Balai Pelatihan Pertanian Jambi, 2021)
Mojogedang sub-district is a center for organic rice production in Karanganyar and is known as a pilot for organic rice cultivation by other regions, with a production size of 803.93 tons/harvest based on 2020 data from the Karanganyar Organic Farmers Association. However, not all farmers have implemented organic farming from upstream to downstream. This study aims to examine the attitudes of rice farmers towards the application of organic agriculture, to examine the factors shaping the attitudes of rice farmers towards the application of organic agriculture, and to examine the influence of the factors forming attitudes towards the attitudes of rice farmers towards the application of organic agriculture. This research uses quantitative methods. The location selection was done by purposive method, namely Mojogedang District, Karanganyar Regency. Sampling with the proportional stratified random sampling method of 80 farmers. The data analysis used is the frequency distribution and Multiple Linear Regression. The results showed that: (1) the attitude of the farmers was in a good category. (2) The factors forming the attitude of farmers in this study include formal education, non-formal education, experience, land area, mass media, group values ​​, and the economic environment. (3) There is a significant effect of non-formal education, land area, group values ​​, and the economic environment on the attitude of rice farmers towards the application of organic agriculture. There is an insignificant effect of formal education, experience, and mass media on the attitude of rice farmers towards the application of organic agriculture.